AN ANALYSIS OF LANGUAGE STYLE IN SONG LYRIC: “HEAT WAVES” BY GLASS ANIMAL - Nur Alve Gina; Muhammad Muntazero Shidqi; Muhammad Hilmi Fauzan; Shafira Hanna Chairina; Ahmet Serhat Uçar (Universitas Lambung Mangkurat, 2022)
The objective of this research is to know and learn more about the language style in figurative language in the lyrics of the song on the song by Glass Animal, which is entitled Heat Waves and can also provide information about the style of language in the lyrics of the song, which means that further researchers can continue further research. The results of this study are (1) Personification: 1; (2) Hyperbole: 2; (3) Alliteration: 1; (4) Assonance: 4; (5) Irony: 1; (6) Anaphora: 2; and (7) Repetition: 3. Based on the result of study, there are 14 figurative languages in the lyrics of